Solid Waste Management Cost Function Analysis in Industrialising Cities: Lessons from the Healthcare Sector. (July 2019) - Parthan, S. R.; Milke, M. W.; Sheerin, I.
Abstract: Better solid waste management (SWM) is a critical need for many industrialising cities in the world, with institutional and financial issues critical to improving management. Great progress was made from 1970–2000 in estimating the costs for healthcare in industrialising cities, while to date very little progress has been made in improving cost function analyses on SWM. The similarities between the two sectors are strong, and the history of healthcare cost function analysis used to elucidate a pathway to improved cost function analyses for industrialising cities. The following cost function issues are explored: economy of scale, marginal cost analysis, cost function analysis, economies of scope, relationship between size of service provider and costs, accounting for outpatient and informal sector activities, input prices and ownership and control. The recommendation is that future work on SWM cost analysis should prioritise (1) analysis of which variables need to be included or can be excluded in cost function analysis, (2) use of cost functions to analyse questions related to service provision and (3) collection of more and more appropriate data to allow development of cost functions analysis methods specifically suited to SWM in industrialising cities.